(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of this study was to determine the common abdominal surgical procedure causing postoperative adhesive intestinal obstruction, and outcome of its surgical management. Study Design: Retrospective as well as prospective analysis. Place and Duration of Study: This study was conducted in the Department of Surgery, Khawaja Muhammad Safdar Medical College, Sialkot from June 2010 to November 2015. Materials and Methods: Patients operated on for intestinal obstruction with at least one abdominal surgical scar were included in the study. A total of 152 patients were eligible, all ages were eligible irrespective of gender. A minimum of 6 months follow up was set for inclusion in the study. Patients with intestinal obstruction presenting with surgical scars for renal, ureteric and urinary bladder surgery were not included as these surgeries did not involve opening of peritoneum. Patients with Crohn's disease, ulcerative colitis, known malignancies, a past history of abdominopelvic irradiation were excluded. Patients with less than 6 months follow up were excluded from the study. Results: Out of 152 patients, 74 (48.68%) surgeries for appendicular pathologies, 18 (11.84%)lower segment caesarean section and 9 (5.92%) total abdominal hysterectomy were the main pathologies causing obstruction; while patients had recurrence in 11(7.23%) and 8(5.26%) mortality. Conclusion: Operated adhesive postoperative intestinal obstruction proves to be a clinical entity with high incidence and specific risk factors of recurrence: age <40 years, presence of adhesion or matted adhesion, and postoperative surgical complications. Infected cases of appendicitis, enteric perforations, lower segment caesarean section and total abdominal hysterectomy are the main causes and the treatment may lead to stoma formation, recurrence and mortality.